Dampak Psikologis Pada Remaja Yang Mengalamai Cyberbullying: - - Luthfiyanti Harinsa Putri; Siti Ina Savira (Universitas Negeri Surabaya, 2023)
The current digital era is getting faster, there needs to be vigilance in receiving incoming information both in providing information and the activities of netizens who comment on each other. However, it cannot be denied that posts shared via social media can influence the public in both prosocial and antisocial behavior. The definition of cyberbullying from the point of view of victims of acts of bullying carried out on social media networks is in the form of hacking personal accounts, getting insults, insults, and even verbal harassment on social media. The research proposed discusses the existence of a psychological impact on adolescents that cannot be separated from social media and interactions that exist in cyberspace without knowing the impact that will occur in the future. The purpose of this research is to determine whether there is a psychological impact on adolescents who experience cyberbullying, as advances in technology are increasing access to facilitate networking in cyberspace. This research topic focuses on adolescents who have experienced cyberbullying on social media, this is done to see what impact cyberbullying has on adolescents who are still in transition to adulthood.